NEW START: THE LIFE EXPERIENCES OF RECOVERING SUICIDAL ADOLESCENTS - Hui-ping Han; Cheng-hui Chou; I-Chao Liu; Jiin-Ru Rong; Shujen Shiau (European Scientific Journal, ESJ, 2014)
Background: Suicide is a serious global health problem and the second leading cause of death for adolescents in Taiwan. Previous studies have typically explored the causes of suicide; however, scant research has considered suicide recovery contexts, leading to the inability to developing effective suicide prevention strategies.Aim: Exploring the life experiences of adolescents during their suicide recovery processes.Method: A descriptive phenomenology research design was employed. The participants comprised 6 outpatient young adult who possessed histories of suicide and recovering from attempted suicide. Semi-structured, one-on-one in-depth interviews were conducted and Colaizzi’s (1978) methods were used for data analysis. Results: The main identified dimension was “new start” which comprised the following five major themes: conversion of suicidal thoughts, awareness of change, loving attachments, the emotional regulation, and the future prospects. Conclusion: Although adolescents are a high-risk population for suicide, they demonstrate recovery power. The results of this study should provide a reference for professional personnel to assist teenagers in recognizing and using internal and external resources, discovering the value of life and hopes for the future, and reducing the risk of suicide.